2002
DOI: 10.1103/physreve.65.036405
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of electromagnetic wave transformation in a time-varying magnetoplasma medium

Abstract: The transformation of a circularly polarized electromagnetic wave in a magnetoplasma medium with increasing plasma density is considered. The wave propagates along the static magnetic field. Complete analysis, including ion motion, is given both for slow (compared to the wave frequency) and rapid ionization rate. In the case of slow temporal variation of the plasma density, a relation between the energy of the wave and its frequency, which is conserved during the plasma creation process (adiabatic invariant), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In a theoretical work, Berezhiani et al showed that the interaction of a laser pulse with a nonstationary semiconductor plasma can lead to a variety of interesting phenomena, including the controlled upshifting of the laser frequency, which could lead to the possibility of tunable lasers over a wide range of frequencies, and the trapping (nonpropagation) of a substantial part of the incident pulse [19]. The propagation of an electromagnetic wave along a planar wave-guiding structure containing time-varying plasma was considered by Bakunov et al They found some quantities (adiabatic in-16 variants) that relate the energy of the wave and its frequency to be conserved during the process of the plasma density variation on condition that the time scale of the variation is much greater than the wave period (adiabatic approximation) [20,21].…”
Section: Previous Studies In the Microwave Regionmentioning
confidence: 99%
“…In a theoretical work, Berezhiani et al showed that the interaction of a laser pulse with a nonstationary semiconductor plasma can lead to a variety of interesting phenomena, including the controlled upshifting of the laser frequency, which could lead to the possibility of tunable lasers over a wide range of frequencies, and the trapping (nonpropagation) of a substantial part of the incident pulse [19]. The propagation of an electromagnetic wave along a planar wave-guiding structure containing time-varying plasma was considered by Bakunov et al They found some quantities (adiabatic in-16 variants) that relate the energy of the wave and its frequency to be conserved during the process of the plasma density variation on condition that the time scale of the variation is much greater than the wave period (adiabatic approximation) [20,21].…”
Section: Previous Studies In the Microwave Regionmentioning
confidence: 99%
“…If the characteristics of a medium vary in time by external perturbations, quantum light waves propagating through it may exhibit nonstatic properties [1][2][3][4][5][6][7][8]. Then, the shapes of the waves would be modified through the change of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The energetics of electromagnetic transformation in a time-varying magnetized plasma medium has been studied (Bakunov and Grachev 2002). Herein, the imposition of a static magnetic field affords the possibility of an extra control parameter in a laboratory plasma.…”
Section: Introductionmentioning
confidence: 99%